Regulatory Instruments and Their Effects on Investment Behavior - Burns, Phil; Riechmann, Christoph (World Bank, Washington, D.C., 2013)
Regulatory instruments have long been understood to have a powerful effect on investment, and part of the motivation for introducing higher-powered regulatory regimes and contracts was to reduce incentives for inefficiency and over-investment (gold plating) inherent in cost-plus regulatory schemes. In practice, the mix of incentives and the institutional framework that make up a higher-powered regulatory regime can also lead to unintended distortions on investment behavior. The authors examine the key drivers of investment behavior and provide some examples of how these drivers have affected investment in practice. They conclude with a set of key areas and interrelationships that are at the core of a regulatory settlement, and therefore need to be designed appropriately to drive efficient investment behavior.